Development of SELASAR Learning Media to Improve Elementary School Students Social Skills - Aldy Ferdiyansyah; Bagus Aulia Iskandar (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Abstract: The development of the digital era presents challenges for elementary school students in developing social skills amid the growing tendency toward technology based interactions, creating a need for learning media that align with digital generation characteristics while actively encouraging direct social interaction. This research intends to design and evaluate the efficacy of SELASAR learning media, which combines the classic snakes and ladders game with augmented reality technology to enhance social skills in elementary school students. The research utilized a Research and Development framework based on the DDD-E model, which includes the stages of decide, design, develop, and evaluate. Product trials were conducted using five indicators of social skills: peer relationship, self-management, academic skills, compliance, and affirmation. The results showed that the peer relationship aspect achieved 72.5% and was categorized as good, self-management reached 90% and was categorized as very good, academic skills achieved 81.25 percent and were categorized as very good, compliance reached 72.5% and was categorized as good, and affirmation achieved 76.25% and was categorized as very good. These findings indicate that SELASAR learning media are effective and practical for addressing challenges related to the development of social skills among elementary school students through interactive and technology integrated learning. Abstrak: Perkembangan era digital menghadirkan tantangan bagi siswa sekolah dasar dalam membangun keterampilan sosial di tengah kecenderungan interaksi berbasis teknologi, sehingga diperlukan media pembelajaran yang selaras dengan karakteristik generasi digital sekaligus mendorong interaksi sosial. Penelitian ini bertujuan mengembangkan dan menguji efektivitas media pembelajaran SELASAR sebagai integrasi permainan ular tangga tradisional dengan teknologi augmented reality untuk meningkatkan keterampilan sosial siswa sekolah dasar. Penelitian menggunakan metode Research and Development (R&D) dengan model DDD-E yang meliputi tahap decide, design, develop, dan evaluate. Uji coba produk berdasarkan lima indikator keterampilan sosial menunjukkan hasil sebagai berikut: (1) aspek peer relationship dengan persentase skor 72,5% tergolong baik; (2) aspek self-management dengan persentase skor 90% tergolong sangat baik; (3) aspek akademik dengan persentase 81,25% tergolong sangat baik; (4) aspek kepatuhan dengan persentase skor 72,5% tergolong baik; (5) aspek penegasan dengan persentase 76,25% tergolong sangat baik. Media pembelajaran SELASAR terbukti efektif dan praktis digunakan dalam menjawab permasalahan terkait pengembangan keterampilan sosial siswa sekolah dasar melalui pembelajaran.